Microporosity formation and dendrite growth during solidification of aluminum alloys: Modeling and experiment. (January 2020) - Zhang, Qingyu; Sun, Dongke; Pan, Shiyan; Zhu, Mingfang
Highlights: A coupled model is developed to simulate dendrite growth and bubble formation. Hydrogen concentration evolution and bubble movement are visualized. Differences between 2-D and 3-D simulations of bubbles and dendrites are analyzed. The 3-D simulation results compare well with the in situ experimental observation. Abstract: A coupled lattice Boltzmann-cellular automaton-finite difference (LB-CA-FD) model is proposed for the simulations of hydrogen porosity formation during dendritic solidification of binary hypoeutectic aluminum alloys. The present model involves the effect of hydrogen and solute partitioning at the solid/liquid interface, and the transport of hydrogen and solute concentrations as gas bubbles and dendrites grow in two and three dimensions. The dendrite growth and solute transport are simulated using a CA-FDM approach. The nucleation, growth, and movement of gas bubbles, as well as the transport of hydrogen, are calculated using the multi-phase LB model. After model validation by the tests of Laplace's law and contact angle simulations on smooth and rough solid surfaces, the proposed model is applied to simulate the temporal evolution of hydrogen porosities and their interaction with dendrites during solidification of an Al-4 wt% Cu alloy. The simulated morphologies of gas pores and dendrites compare reasonably well with the experimental micrograph reported in the literature. The simulation results show that the gas bubbles nucleate at the roots of secondary dendrite arms preferentially. The competitive growth between the bubbles is visualized and found to be coherently controlled by bubble size, hydrogen supersaturation, and local hydrogen concentration in liquid. The simulations of microporosity formation together with columnar dendrite growth during directional solidification of an Al-4 wt% Cu alloy are carried out in two and three dimensions. It is found that the bubbles could move in the interdendritic liquid channel in the two-dimensional case. In the three-dimensional simulation, however, the bubbles are probably pinned by the secondary arms and thereby remain stationary. The three-dimensional simulation results are identical with the in situ experimental observation.